The Educational Experiences of Deaf Students in Ipoh, Malaysia - Lee, Wan Ying; Tan, Joanna Tjin Ai; Kok, Jin Kuan (Jurnal Pendidikan Bitara UPSI, 2021)
Ninety percent of children with hearing impairment are born to hearing parents. Ready or not, these new parents face challenges raising a deaf child. One of the challenges include making important decisions regarding the child’s mode of communication and education – whether to strive towards hearing and speech or to choose an alternative of sign language. In order to provide the best learning opportunity for these children, the Ministry of Education in Malaysia has presented three educational options – Special education schools, Special Education Integration Programs, and Inclusive Education Programs. The parental choice of education for their child varies according to what seems the “best” for the child and family’s situation. However, how well do deaf students adapt to the chosen educational choice of parents? This study explored the educational experiences (primary, secondary and tertiary) and challenges of deaf students. Six deaf adults aged between 20 – 37, from Ipoh were interviewed. Deaf adults were selected as they were able to better articulate their growing up experiences. This study employed the ethnographic approach, where interviews and participatory observations were carried out as data collection methods. Using thematic analysis, two main themes emerged from the participants’ experiences– “journey of exploration” and a “journey of adapting”. During their journey of exploration, deaf students explained their struggle to keep up as they were excluded from communications. Their journey of adaptation included seeking equal relationships and meaningful connections. The results of this study provided insights to the challenges and struggles of deaf students, which would be useful to educators as they facilitate student learning and strive to provide a more supportive learning environment for deaf students.